Floristic classifications and bioregionalizations are not predictors of intra-specific evolutionary patterns - Patrick S. Fahey; Richard J. Dimon; Marlien M. van der Merwe; Jason G. Bragg; Maurizio Rossetto (Nature Communications)
Abstract The relationship between intra-specific and inter-specific patterns and processes over evolutionary time is key to ecological investigations. We examine this relationship taking an approach of focussing on the association between vegetation and floristic classifications, summaries of inter-specific processes, and intra-specific genetic structuring. Applying an innovative, multispecies, and standardised population genomic approach, we test the relationship between vegetation mapping schemes and structuring of genetic variation across a large, environmentally heterogenous region in eastern Australia. We show that intra-specific genetic variation shows limited correspondence to vegetation and floristic classifications and is better explained by distance between sampled populations and the location of biogeographical features which limit gene flow. Mapping schemes with contiguous mapping classes, particularly larger ones, were more predictive of genetic lineages, whether based on environmental factors or not, than geographically non-contiguous schemes. We conclude that vegetation and floristic classifications are not closely correlated with intra-specific genetic patterns, showing that intra-specific processes are not recapitulated by inter-specific floristic assembly processes. This study showcases the need to implement landscape level evolutionary patterns, based on species specific datasets, in restoration and conservation activities.